Women Entrepreneurship Through E-Business - Azlizan Talib; Mohd Nazaruddin Yusoff (International Journal of Supply Chain Management, 2019)
This study is to examine the perception of entrepreneurship among women through e-business in rural area. It has become a phenomenon that has gained a lot of attention and has the potential to provide economic opportunities that can help in generating lucrative income. However, the percentage rate of women participation in economic development is still low. These problems are linked to gender issues that are hard to eradicate from the local community's thinking. Women are also seen as less interested in conventional entrepreneurship as it imposed a high risk and require their high commitment. To solve this problem, women began to respond positively to e-business. Among the objectives of the study are to identify the level of understanding, prospects and issues and e-business challenges and identify the implications of e-business in influencing the people’s live. In order to meet the predetermined objective requirements, this study uses a quantitative approach, a questionnaire to collect data from 150 rural women. The results show that e-business has a positive implication in influencing the lifestyle of the women community that saves the consumer's time; but also has a negative implication of reducing social interaction among society. Hence, the e-business field should always be addressed, developed and tailored to help the increase of the participation of women in entrepreneurship in the rural area.